Investigating Induced Infiltration by Municipal Production Wells Using Stable Isotopes of Water (δ18O and δ2H), Four Mile Creek, Ohio - Idah Ngoma; Jonathan Levy; Jason A. Rech; Tedros M. Berhane (Hydrology)
Many municipalities around the world place their production wells in shallow alluvial aquifers that are adjacent to streams. Pumping these wells then induces the infiltration of surface water into the aquifer, allowing the greater extraction of water without significantly depleting the aquifer. However, induced infiltration poses a risk of introducing contamination from surface water into groundwater systems. The goal of this study was to quantify the amount of induced infiltration due to municipal pumping at the Four Mile Creek well field in Oxford, Ohio, using stable isotopes of water oxygen (δ18O) and deuterium (δ2H). In areas of municipal pumping, we sampled water from the production wells, Four Mile Creek, and from monitoring wells that we hypothesized to be both influenced and not influenced by induced infiltration. Samples were collected over 10 months in 2012 and over 12 months in 2021. In 2012, surface water δ18O values ranged from −3.89 to −8.04‰, and δ2H ranged from −26.55 to −55.65‰ at sampling sites. PW1 δ18O values ranged from −4.71 to −7.39‰ with a mean of −6.61 and −32.01 to −47.86‰ with a mean of −42.74‰ for δ2H. PW2 δ18O values ranged from −5.74 to −7.34‰, with a mean of −6.45‰, and δ2H ranged from −36.29 to −47.82‰ with a mean of −42.43‰. PW3 had lower values of both δ18O and δ2H, ranging from −6.36 to −8.02‰ and −47.7 to −40.35‰, and with means of −7.08 and −45.11, respectively. In 2021/2022, surface water δ18O values ranged from −5.32 to −7.93‰, and the δ2H ranged from −36.14 to −50.56‰. PW1 δ18O values ranged from −6.15 to −7.54‰ with a mean of −7.13‰, and δ2H ranged from −43.52 to −49.01‰ with a mean of −45.99‰. PW2 δ18O values ranged from −5.72 to −7.34‰, with a mean of −6.70‰, and δ2H ranged from −36.69 to −46.14‰, with a mean of −43.61‰. Using the time averaged values of δ18O of groundwater, production wells and surface water, the percentages of surface water resulting from induced infiltration in 2012 were 57%, 59% and 15% at the three wells, respectively, while in 2021, PW1 had 35% and PW2 91%. The amount of induced infiltration was apparently related to the pumping rates of the production wells, the length of time of pumping and the distance between Four Mile Creek and production wells. Our results indicate that stable isotopes of water provide a reliable method of quantifying groundwater/surface water interaction in alluvial aquifers.